Desensitization therapy using 'Mariana Castells' protocol in a patient with multiple autoimmune disorders- does it work? - Syed Raza Shah; Terance Millan; Sardar Muhammad Alamzaib; Sue-Wei Luu (Greater Baltimore Medical Center, 2019)
Clinical use of antibiotics is becoming more widespread with each passing day for various infectious diseases. This has caused an abrupt increase in hypersensitivity reactions linked to these drugs, sometimes preventing the use of first-line therapies. In these patients, clinical presentation may vary from mild skin infections to life-threatening anaphylactic reactions. Our patient is a 30 year old female with past medical history significant for mast cell activation syndrome and multiple autoimmune diseases who presented with chief complaint of fever. Patient was diagnosed with MSSA bacteremia requiring the start of an antibiotic regimen. Mariana castells protocol was used for desensitizing the patient before starting her on antibiotic regimen. Patient was desensitized in 2 days using the standard 12-step protocol and started on cefazolin for her long-term treatment of the infection. No acute episodes of drug hypersensitivity were reported. During the course of her hospital admission, she improved significantly with no complications. Our patient having a history of both multiple autoimmune diseases and mast-cell activation syndrome tolerated the protocol well with no complications. Appropriate treatment of the reactions including epinephrine use and management with personalized desensitization protocols can enhance the quality of life, life expectancy, and safety of an increasing at risk population of patients with infectious diseases allergic to their best medications. Protocols, such as mariana castells, are completely safe in autoimmune disorders and should be utilized as the standard of care in appropriate patient population.